2014
DOI: 10.1111/pai.12190
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections and atopic dermatitis among Venezuelan Warao Amerindian pre‐ school children

Abstract: Background: We evaluated the influence of intestinal parasitic infection on food sensitization associated to the severity of Atopic Dermatitis (AD) in a group of Warao Amerindian pre-school children. Methods: Feces examinations were performed in fresh stool specimens. Diagnosis of AD was done according to Hannifin and Rajka criteria and SCORAD index. Skin prick tests (SPT) were performed using extracts of cow's milk (CM), hen's egg (HE), Dermatophagoides pteronyssinus and Dermatophagoides farinae . Serum CM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…However, the prevalence of Giardia duodenalis in our study (up to 26 % in the 2- to 4-year-olds at study week 28) was higher than the prevalence of Giardia in those two studies [ 49 , 50 ]. Intestinal parasites may have contributed to the high incidence of AM in our cohort, as suggested in a large survey in Brazilian children < 5 years [ 51 ], including Giardia, which was shown to be a risk factor for allergy [ 52 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, the prevalence of Giardia duodenalis in our study (up to 26 % in the 2- to 4-year-olds at study week 28) was higher than the prevalence of Giardia in those two studies [ 49 , 50 ]. Intestinal parasites may have contributed to the high incidence of AM in our cohort, as suggested in a large survey in Brazilian children < 5 years [ 51 ], including Giardia, which was shown to be a risk factor for allergy [ 52 ].…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have reported a relatively high prevalence of parasitemia in children with allergic diseases. As there is some evidence that these may aggravate the disease course ( 65 , 277 279 ), patient management should include deworming strategies when required.…”
Section: Discussionmentioning
confidence: 99%
“…These levels were profoundly increased by Ascaris lumbricoides co-infection [83]. The same group also found that giardiasis may enhance the outcome of atopic dermatitis allergic reactions in school children [84]. But G. duodenalis infection was also found to reduce granulocyte infiltration in an in vivo model of bacterial toxin-induced colitis and attenuates inflammation in human intestinal tissue suggesting modulating immune responses during giardiasis [85].…”
Section: Adaptive Immune Responsesmentioning
confidence: 90%